Gaya Kepemimpinan Kepala Desa Madani Kecamatan Sorkam Barat Dalam Meningkatkan Produktivitas Kinerja Aparatur Pemerintah Desa - Edo Joshep Putra Silaban; Walid mustafa; Evi Yunita Kurniaty (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2023)
Madani Village is located in West Sorkam Barat District, Tapanuli Tengah Regency. This research started from the researcher's interest in seeing the importance of a leader's leadership style as a determining factor in the success or failure of an organization, both governmental and non-governmental, especially in Madani Village, Sorkam Barat District, Tapanuli Tengah Regency. aims to see Most of the people how the leadership style of the village head in increasing the productivity of village apparatus performance and what factors increase the productivity of village government apparatus performance in Madani Village, Sorkam Barat District, Tapanuli Tengah Regency. The results of the study indicate that the Madani village head applies a mixed, democratic and supervisory leadership style, with this leadership style strengthening the relationship between leaders and subordinates such as involving subordinates in decision making. Then it is strengthened by the existence of several factors driving the productivity of the performance of village government apparatus such as ability or skill factors, cultural and environmental factors and leadership style factors, and the most dominant of these three factors is the leadership style factor because with a leader there is someone who gives encouragement, input. and guidance to subordinates or apparatus at work.